2018
DOI: 10.1002/jcp.26556
|View full text |Cite
|
Sign up to set email alerts
|

The MAPK‐activator protein‐1 signaling regulates changes in lung tissue of rat exposed to hypobaric hypoxia

Abstract: This study reports the role of MAPKs (JNK, ERK, and p38), and activator protein-1 (AP-1) transcription factor in the hypobaric hypoxia induced change in lung tissue. Healthy male Sprague-Dawley rats were exposed to hypobaric hypoxia for 6, 12, 24, 48, 72, and 120 hr. Hypoxia resulted in significant increase in reactive oxygen species (ROS), vascular endothelial growth factor (VEGF) and decreased nitric oxide (NO), these act as signaling molecules for activation of MAPK and also contribute in development of vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 64 publications
3
19
0
Order By: Relevance
“…These miRNAs and mRNAs may play an important role in the development of HAR.FOS, consisting of c-Fos, FosB, Fra1 and Fra2[35], was significantly downregulated in our hypoxia-cultured HRMECs. In the lung tissues of hypoxic rats, the expression of c-Fos and FosB was significantly decreased[36], which is consistent with our results. C-Fos promotes the development of inflammatory diseases such as arthritis[37], but it also inhibits inflammation in myeloid and lymphoid cell lineages[38].…”
supporting
confidence: 92%
“…These miRNAs and mRNAs may play an important role in the development of HAR.FOS, consisting of c-Fos, FosB, Fra1 and Fra2[35], was significantly downregulated in our hypoxia-cultured HRMECs. In the lung tissues of hypoxic rats, the expression of c-Fos and FosB was significantly decreased[36], which is consistent with our results. C-Fos promotes the development of inflammatory diseases such as arthritis[37], but it also inhibits inflammation in myeloid and lymphoid cell lineages[38].…”
supporting
confidence: 92%
“…Similar results have been found in periodontal ligament stem cells (He et al, 2016;Kabiri et al, 2018). Previous studies have shown that the sodium hydrosulfide-mediated inhibition of the cigarette smoke-induced phosphorylation of ERK, JNK and p38 MAPK may be a novel strategy for the treatment of chronic obstructive pulmonary fibrosis through the inhibition of inflammation, epithelial cell injury and apoptosis (Guan et al, 2020;Shologu et al, 2018;Singh et al, 2018). Therefore, we focused our further studies on MAPK signaling.…”
Section: Speculation Of the Hypoxia Signaling Pathway Affecting The Regulation Of Atii Cellssupporting
confidence: 78%
“…The increased RI was indicative of distal vasoconstriction, such as constriction at the precapillary or capillary level that resulted in decreased blood flow in the retinal capillary bed, though the exact degree of blood flow reduction was not measured. A previous study reported that abnormal vasoconstriction caused by hypoxia occurs along with increases in VEGF [61] and inhibitors of the VEGF pathway have been regarded as promising therapeutic agents for relieving vasoconstriction [62]. To our surprise, oral administration of SCU in diabetic rats not only decreased retinal angiogenesis but also corrected abnormal vasoconstriction by inhibiting the expression of VEGF.…”
mentioning
confidence: 77%